Chiral luminescent material with space charge transfer effect and application thereof
Patent Information
- Application Number
- CN202311096272.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-08-29
AI Technical Summary
2019年,Tang及其同事报道了第一种具有CPL特性的TADF聚合物,分别在聚合物骨架中引入手性侧链和TADF侧链,实现了不对称因子(|glum|)高达2.0×10-3的CP-TADF性能,但文章未对聚合物的CPEL性能进行研究
[0012]1、将具有分子内空间电荷转移的热活化延迟荧光材料与手性联萘衍生物进行聚合,构筑系列新型的轴手性聚合物发光材料;在保持发光单元的光物理特性的情况下赋予其手性;
Smart Images

Figure QLYQS_1 
Figure BDA0004419205020000031 
Figure BDA0004419205020000061
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic electroluminescent materials technology, and specifically discloses a class of chiral luminescent materials with space charge transfer effect and their applications. Background Technology
[0002] Circularly polarized luminescent materials have shown broad application prospects in recent years in fields such as optical data storage, chiral sensing, bio-responsive imaging, asymmetric synthesis, and chiral materials. Besides applications of circularly polarized photoluminescence, the development of circularly polarized electroluminescence (CPEL) has also attracted widespread attention and is considered even more valuable in optoelectronic technology. Since Meijer et al. first reported circularly polarized polymer light-emitting diodes (CP-PLEDs) in 1997, CPELs in CP-PLEDs have developed rapidly. However, due to a theoretical internal quantum efficiency (IQE) of 25%, conventional fluorescent polymer materials cannot achieve satisfactory performance in CP-PLED devices. To achieve more efficient CPELs, chiral phosphorescent complexes with a theoretical IQE of 100% have been used as luminescent materials for corresponding devices. However, phosphorescent materials still face problems such as high cost, environmental issues, and instability of coordination bonds.
[0003] As a third-generation luminescent material, thermally activated delayed fluorescence (TADF) emitting materials with a purely organic molecular structure can achieve the same theoretical IQE as phosphorescent emitting materials, making them a promising pure organic material for manufacturing organic light-emitting diodes (OLEDs). Unlike traditional fluorescent emitting materials, TADF emitting materials consistently possess a sufficiently small singlet-triplet bandgap (ΔE) due to the well-separated distribution of the highest occupied molecular orbitals (HOMOs) and lowest unoccupied molecular orbitals (LUMOs). ST The voltage is less than 0.3 eV. Therefore, triplet excitons can be fully utilized through upconversion of the reverse systemic crossover (RISC) process without the need for additional energy supply, thus improving exciton utilization.
[0004] CP-OLED devices fabricated using chiral TADF emission materials can easily achieve high-efficiency CPELs. Compared with small-molecule organic emission materials, polymers have advantages in thermal stability, structural diversity, and device fabrication. In 2019, Tang and colleagues reported the first TADF polymer with CPL properties, introducing chiral side chains and TADF side chains into the polymer backbone, respectively, achieving an asymmetry factor (|g... lum |) Up to 2.0×10 -3The article describes the CP-TADF properties, but does not investigate the CPEL properties of the polymer. In 2021, Chen Chuanfeng's research group adopted a chiral donor-acceptor (D*-A) copolymerization strategy and reported for the first time a CP-PLED based on a chiral TADF polymer. This material has a unique three-dimensional rigid chiral donor unit and uses diphenyl sulfone or benzophenone as the acceptor. This polymer exhibits a strong CPL signal in a 10 wt% mCP film, with a |g PL The value can reach 1.9 × 10 -3 With the continuous optimization of chiral luminescent molecular structures, more and more highly efficient CP-PLEDs are emerging, making chiral luminescent materials one of the most popular research areas. However, simultaneously achieving high efficiency and high gamma-ray emission is a challenging task. lum However, there are few reports on molecules with high efficiency and high g-value. Therefore, how to regulate the molecular structure to obtain molecules that combine high efficiency and high g-value is a key research area. lum Finding the optimal value for CP-PLEDs is one of the current challenges for researchers. Summary of the Invention
[0005] To further reduce ΔE ST This invention aims to obtain more efficient TADF materials. Using a binatene derivative as the chiral source, diphenyl sulfone or benzophenone as the electron acceptor, and acridine as the electron donor, a novel class of axial chiral luminescent materials with space charge transfer effects was synthesized via the Suzuki-Miyaura reaction. Introducing space charge transfer characteristics into chiral polymer luminescent materials results in materials exhibiting a significant space charge transfer effect. In this scheme, diphenyl sulfone or benzophenone acts as the electron acceptor, and acridine as the electron donor. The combination of these two facilitates the separation of the highest occupied orbital (HOMO) and lowest occupied orbital (LUMO) of the molecule, which not only reduces the band gap difference of the singlet triplet state but also improves the luminescent efficiency of the material.
[0006] This invention first synthesizes a novel class of axially chiral luminescent materials with space charge transfer effect, using a naphthalene derivative as the chiral source, diphenyl sulfone or benzophenone as the electron acceptor, and acridine as the electron donor. These materials have the following structure:
[0007]
[0008] Using naphthalene derivatives as chiral sources, diphenyl sulfone or benzophenone as electron acceptors, and acridine as an electron donor, the structure-property relationship of the materials was systematically studied by altering the electron-withdrawing ability of the acceptors and the steric hindrance between the two monomers during polymerization.
[0009] This invention also provides the application of novel axially chiral luminescent materials as luminescent layer materials for organic electroluminescent diodes, which can obtain solution-processed organic electroluminescent devices with excellent luminescent performance.
[0010] The mass percentage of chiral luminescent material used as a dopant in the luminescent layer is 10-30 wt%.
[0011] The technical advantages of this invention are:
[0012] 1. A series of novel axially chiral polymeric luminescent materials are constructed by polymerizing thermally activated delayed fluorescence materials with intramolecular space charge transfer and chiral binaphthyl derivatives; chirality is imparted to them while maintaining the photophysical properties of the luminescent unit.
[0013] 2. Using sulfone or benzophenone as the electron acceptor and acridine as the electron donor, their combination facilitates the separation of the highest occupied orbital (HOMO) and lowest occupied orbital (LUMO) of the molecule, which helps to reduce ΔE. ST It is easy to obtain TADF materials and can improve the luminous efficiency of the materials;
[0014] 3. The effects of the acceptor's electron-withdrawing ability on the retention of TADF properties in polymers and the effect of using the benzene ring as a π-bridge to reduce the steric hindrance between the two monomers during polymerization on the polymer molecular weight were systematically studied, and a series of yellow-green chiral TSCT thermally active delayed fluorescence polymer materials were obtained. Attached image description:
[0015] 【 Figure 1 The figures show the thermogravimetric curves of compounds (R) / (S)-F, (R) / (S)-BP-TATC and (R) / (S)-BPh-DPS obtained in Example 1 of this invention.
[0016] 【 Figure 2 The images show the UV-Vis absorption and photoluminescence spectra of compound (R) / (S)-F obtained in Example 1 of this invention in toluene solution and in a 10% doped PMMA film (wherein, (a) is the UV-Vis absorption and photoluminescence spectrum of compound (R) / (S)-F in toluene solution, and (b) is the photoluminescence spectrum of compound (R) / (S)-F in a 10% doped PMMA film).
[0017] 【 Figure 3 The images show the UV-Vis absorption and photoluminescence spectra of compound (R) / (S)-BP-TATC in toluene solution and the photoluminescence spectrum of compound (R) / (S)-BP-TATC in a 10% doped PMMA film prepared in Example 1 of this invention (wherein, (a) is the UV-Vis absorption and photoluminescence spectrum of compound (R) / (S)-BP-TATC in toluene solution, and (b) is the photoluminescence spectrum of compound (R) / (S)-BP-TATC in a 10% doped PMMA film).
[0018] 【 Figure 4The images show the UV-Vis absorption and photoluminescence spectra of compound (R) / (S)-BPh-DPS obtained in Example 1 of this invention in toluene solution and in a 10% doped PMMA film (wherein, (a) is the UV-Vis absorption and photoluminescence spectrum of compound (R) / (S)-BPh-DPS in toluene solution, and (b) is the photoluminescence spectrum of compound (R) / (S)-BPh-DPS in a 10% doped PMMA film).
[0019] 【 Figure 5 The image shows the photoluminescence spectra of compound (R) / (S)-F obtained in Example 1 of this invention in five solutions: toluene, chloroform, tetrahydrofuran, dichloromethane, and N,N-dimethylformamide.
[0020] 【 Figure 6 The image shows the photoluminescence spectra of compound (R) / (S)-BP-TATC prepared in Example 1 of this invention in five solutions: toluene, chloroform, tetrahydrofuran, dichloromethane, and N,N-dimethylformamide.
[0021] 【 Figure 7 The image shows the photoluminescence spectra of compound (R) / (S)-BPh-DPS prepared in Example 1 of this invention in five solutions: toluene, chloroform, tetrahydrofuran, dichloromethane, and N,N-dimethylformamide.
[0022] 【 Figure 8 [Image caption: Instantaneous lifetime curve of compound (R) / (S)-F obtained in Example 1 of this invention in a 10% doped PMMA film.]
[0023] 【 Figure 9 The figures show the instantaneous lifetime and delayed lifetime curves of the compound (R) / (S)-BP-TATC prepared in Example 1 of this invention in a 10% doped PMMA film.
[0024] 【 Figure 10 [Image caption: Instant lifetime curve of compound (R) / (S)-BPh-DPS prepared in Example 1 of this invention in a 10% doped PMMA film.]
[0025] 【 Figure 11 [Image caption: Temperature-dependent lifetime curve of compound (R) / (S)-BP-TATC obtained in Example 1 of this invention.]
[0026] 【 Figure 12 The compounds (R) / (S)-F, (R) / (S)-BP-TATC, and (R) / (S)-BPh-DPS prepared in Example 1 of this invention are used in undoped thin films for CPPL and g. PLSpectra of CPPL versus wavelength (where (a) is the CPPL of compound (R) / (S)-F in undoped thin films as a function of wavelength, and (b) is the CPPL of compound (R) / (S)-F in undoped thin films as a function of wavelength). PL Spectra of CPPL versus wavelength in (c) (R) / (S)-BP-TATC in undoped thin films, and spectra of g in (d) (R) / (S)-BP-TATC in undoped thin films. PL Spectra of CPPL versus wavelength in (e) (R) / (S)-BPh-DPS in undoped thin films, and spectra of g in (f) (R) / (S)-BPh-DPS in undoped thin films. PL (Spectrum variation with wavelength).
[0027] 【 Figure 13 [Image showing the relationship between the brightness and maximum external quantum efficiency of compounds (R)-BP-TATC and (R)-F as guests obtained in Example 1 of this invention (wherein, (a) is the electroluminescence spectrum of compound (R)-BP-TATC as a guest doped in the host mCPCN at 10wt%, 20wt%, and 30wt%, (b) is the relationship between the brightness and maximum external quantum efficiency of compound (R)-BP-TATC as a guest, (c) is the electroluminescence spectrum of compound (R)-F as a guest doped in the host mCPCN at 10wt%, 20wt%, and 30wt%, and (d) is the relationship between the brightness and maximum external quantum efficiency of compound (R)-F as a guest).]
[0028] 【 Figure 14 The images show the 1H NMR spectra of compounds (R) / (S)-F, (R) / (S)-BP-TATC, and (R) / (S)-BPh-DPS obtained in Example 1 of this invention (wherein, (a) is the 1H NMR spectrum of compound (R) / (S)-F, (b) is the 1H NMR spectrum of (R) / (S)-BP-TATC, and (c) is the 1H NMR spectrum of (R) / (S)-BPh-DPS). Detailed Implementation
[0029] The following specific implementation examples are intended to further illustrate the present invention, but these specific implementation examples do not limit the scope of protection of the present invention in any way.
[0030] Example 1: Synthesis of chiral luminescent materials:
[0031]
[0032]
[0033] Synthesis of compound SM1
[0034] The following reactants were added sequentially to a 100 mL single-necked flask: potassium carbonate (18.7 g, 135.2 mmol), o-phenanthroline (811 mg, 4.5 mmol), cuprous iodide (857 mg, 4.5 mmol), 1-fluoro-2-iodobenzene (10.0 g, 45.1 mmol), thiophenol (4.6 mL, 45.1 mmol), and 50 mL of analytical grade toluene. The mixture was refluxed at 120 °C for 24 hours under nitrogen protection. After the reaction was complete, the mixture was cooled to room temperature, and the solvent toluene was removed by rotary evaporation. The mixture was then extracted with dichloromethane after adding water, washed three times with water, filtered, and the filtrate was collected. The solvent was then evaporated to dryness. Using pure petroleum ether as the eluent, column chromatography was performed to obtain 7.8 g of a clear liquid, with a yield of 85%. 1 H NMR (500MHz, CDCl3) δ (ppm) 7.55-7.46 (m, 3H), 7.31 (dt, J = 13.3, 4.5Hz, 4H), 7.26-7.18 (m, 2H).
[0035] Synthesis of compound SM2
[0036] SM1 (7.8 g, 38.3 mmol) and 50 mL of glacial acetic acid were added to a 200 mL single-necked flask. Stirring was started, and 50 mL of hydrogen peroxide was added dropwise. The mixture was then refluxed at 100 °C for 12 hours. After the reaction was complete, the mixture was cooled to room temperature, and the reaction solution was poured into 100 mL of water. A white solid precipitated, which was filtered and the residue was collected. Recrystallization from ethanol yielded 5.9 g of a white solid, with a yield of 65%. 1 H NMR(500MHz,DMSO)δ(ppm)8.08(td,J=7.7,1.7Hz,1H),7.96(d,J=8.4Hz,2H),7.85-7.7 3(m,2H),7.67(dd,J=10.7,4.9Hz,2H),7.51(td,J=7.8,0.9Hz,1H),7.46-7.38(m,1H).
[0037] Synthesis of compound SM3
[0038] The following reactants were added to a 100 mL two-necked flask: SM2 (1.0 g, 4.2 mmol), 9,10-dihydro-9,9-dimethylacridine (1.0 g, 5.1 mmol), and 60% sodium hydride (338 mg, 8.5 mmol). After nitrogen protection, 30 mL of freshly distilled tetrahydrofuran was added to the system using a syringe, and the mixture was refluxed at 70 °C for 24 h. After the reaction was complete, the mixture was cooled to room temperature, extracted with saturated brine, washed three times with dichloromethane, filtered, and the filtrate was collected and the solvent was evaporated to dryness. Using petroleum ether and dichloromethane (v / v) as eluent, column chromatography was performed to obtain 640 mg of a white solid, with a yield of 36%. 1H NMR (500MHz, CDCl3) δ (ppm) 8.48 (dd, J=8.0, 1.5Hz, 1H), 7.99 (td, J=7.6, 1.6H z,1H),7.91(td,J=7.8,1.2Hz,1H),7.50(dd,J=8.4,1.1Hz,2H),7.45(dd,J=7 .8,1.4Hz,2H),7.41-7.34(m,2H),7.17(dd,J=8.2,7.6Hz,2H),6.85-6.74(m, 2H),6.67-6.58(m,2H),5.41(dd,J=8.3,0.9Hz,2H),1.78(s,3H),1.66(s,3H). 13 C NMR (126MHz, CDCl3) δ142.38,141.23,139.53,139.16,136.62,134.49,132.77,131.44,129.48, 129.34,128.34,128.31,126.22,126.16,120.70,114.65,36.36,35.54,32.48.MALDI-MS(m / z)of C 27 H 23 NO2Sfor[M] + :calcd.425.14;found,426.31.
[0039] Synthesis of compound SM4
[0040] In a 100 mL single-necked flask, SM3 (800 mg, 1.9 mmol) and 15 mL of anhydrous chloroform solution were added sequentially. N-bromosuccinimide (686 mg, 3.8 mmol) dissolved in 15 mL of anhydrous chloroform was then slowly added dropwise to the flask at 0 °C. The flask was then moved to room temperature and reacted in the dark for 12 h. After the reaction was complete, the solvent was evaporated, and the mixture was precipitated with tetrahydrofuran and methanol. The precipitate was then filtered to give 906 mg of a white solid, with a yield of 82.6%. 1 H NMR (400MHz, CD2Cl2) δ8.45(d,J=7.9Hz,1H),7.76(dt,J=15.3,6.8Hz,2H),7.43(d,J=8.5Hz,2H),7.39(s,2H),7.30(t,J=7. 5Hz,1H),7.17(d,J=6.6Hz,1H),7.07(t,J=7.9Hz,2H),6.63(d,J=6.6Hz,2H),5.32(d,J=8.8Hz,2H),1.68(d,J=13.5Hz,6H).
[0041] Synthesis of compound SM5
[0042] The following reactants were added to a 100 mL two-necked flask: o-fluorobenzophenone (1.0 g, 5.0 mmol), 9,10-dihydro-9,9-dimethylacridine (1.25 g, 6.0 mmol), and 60% sodium hydride (399 mg, 10.0 mmol). After nitrogen protection, 30 mL of freshly distilled tetrahydrofuran was added to the system using a syringe, and the mixture was refluxed at 70 °C for 24 h. After the reaction was complete, the mixture was cooled to room temperature, extracted with saturated brine, washed three times with dichloromethane, filtered, and the filtrate was collected. The solvent was then evaporated to dryness. Using petroleum ether and dichloromethane (2:1 v / v) as eluent, column chromatography was performed to obtain 843 mg of a white solid, with a yield of 43.4%. 1 H NMR (400MHz, CDCl3) δ7.77(dd,J=7.4,6.1Hz,1H),7.70(dd,J=7.6,1.5Hz,1H),7.63(qd,J=4.4,1.9Hz,3H),7.45(d,J=7.8Hz,1H),7.38–7 .29(m,3H),7.16(t,J=7.8Hz,2H),6.99–6.94(m,2H),6.87(td,J=7.6,1.1Hz,2H),6.34(dd,J=8.2,0.9Hz,2H),1.74(s,3H),0.88(s,3H).
[0043] In a 100 mL single-necked flask, SM5 (400 mg, 1.0 mmol) and 15 mL of anhydrous chloroform solution were added sequentially. The synthesis of compound SM6 was carried out at 0 °C.
[0044] N-bromosuccinimide (375 mg, 2.1 mmol) dissolved in 15 mL of anhydrous chloroform was slowly added dropwise to a flask, and the mixture was then placed at room temperature and reacted in the dark for 12 h. After the reaction was complete, the dissolved dichloromethane and methanol were evaporated and allowed to precipitate. The mixture was then filtered to give 200 mg of a yellow solid, with a yield of 35.6%. 1 H NMR(400MHz, CDCl3)δ7.80–7.76(m,1H),7.67(ddd,J=22.0,11.2,4.5Hz,4H),7.46–7.36(m,4H),7 .23(t,J=7.8Hz,2H),7.06(dd,J=8.8,2.2Hz,2H),6.20(d,J=8.8Hz,2H),1.69(s,3H),0.92(s,3H).
[0045] Synthesis of compound (R)-SM7
[0046] In a 200 mL single-necked flask, (R)-binaphthol (5 g, 17.5 mmol), 1,4-dibromo-2,3-difluorobenzene (5.2 g, 19.2 mmol), cesium carbonate (11.4 g, 35 mmol), and 100 mL of anhydrous N,N-dimethylformamide were added sequentially. The mixture was heated to 120 °C and refluxed overnight under nitrogen protection. After cooling to room temperature, water was added, followed by extraction with dichloromethane, washing three times with water, drying to anhydrous magnesium sulfate, filtering, and collecting the filtrate. The solvent was then evaporated to dryness. Column chromatography using petroleum ether and dichloromethane (7:1 v / v) as eluent yielded 4.3 g of a white solid, with a yield of 47.0%. 1 H NMR (400MHz, CDCl3) δ8.00(d,J=8.8Hz,2H),7.95(d,J=8.2Hz,2H),7.60–7.55(m,4H),7.50(t,J=7.4Hz,2H),7.39(t,J=7.5Hz,2H),7.27(s,2H).
[0047] Synthesis of compound (S)-SM7
[0048] Its synthetic route and method are the same as those of compound (R)-SM7.
[0049] Synthesis of compound (R)-SM8
[0050] In a 200 mL single-necked flask, (R)-SM7 (2 g, 3.9 mmol), pinacol diborate (2.1 g, 9.7 mmol), potassium acetate (3.79 g, 39.0 mmol), [1,1'-bis(diphenylphosphine)ferrocene]palladium dichloride (0.14 g, 0.193 mmol), and 50 mL of analytical grade toluene solution were added sequentially. The mixture was refluxed at 110 °C for 24 h under nitrogen protection. After the reaction was complete, the mixture was cooled to room temperature, the solvent was evaporated, water was added, and the mixture was extracted with dichloromethane, washed three times with water, dried over anhydrous magnesium sulfate, filtered, and the filtrate was collected. The solvent was evaporated again. The mixture was then slurried between dichloromethane and methanol, and filtered to give 1.9 g of a white solid, with a yield of 81.2%. 1 H NMR (400MHz, CD2Cl2) δ7.90(t,J=9.3Hz,4H),7.58(d,J=8.8Hz,2H),7.50(d,J=8.3H z, 2H), 7.42 (t, J = 7.3Hz, 2H), 7.33 (dd, J = 15.9, 8.3Hz, 4H), 1.27 (d, J = 2.8Hz, 24H).
[0051] Synthesis of compound (S)-SM8
[0052] Its synthetic route and method are the same as those of compound (R)-SM8.
[0053] Synthesis of compound (R)-SM9
[0054] In a 100 mL single-necked flask, (R)-SM8 (800 mg, 1.3 mmol), p-bromoiodobenzene (1.1 g, 3.92 mmol), potassium carbonate (1.8 g, 13 mmol), tetraphenylphosphine palladium (76 mg, 0.07 mmol), 30 mL tetrahydrofuran, and 15 mL water were added sequentially. The mixture was heated to 80 °C and refluxed for 24 h under nitrogen protection. After cooling to room temperature, water was added, followed by extraction with dichloromethane, washing three times with water, drying over anhydrous magnesium sulfate, filtering, and collecting the filtrate. The solvent was then evaporated to dryness. Using petroleum ether and dichloromethane (8:1 v / v) as eluent, column chromatography was used to obtain 512 mg of a white solid, with a yield of 58.7%. 1 H NMR (400MHz, CDCl3) δ7.91(d,J=8.1Hz,2H),7.84(d,J=8.8Hz,2H),7.55(dd,J=8.9,2 .7Hz,6H),7.51–7.45(m,6H),7.41–7.35(m,2H),7.22(s,2H),6.96(d,J=8.8Hz,2H).
[0055] Synthesis of compound (S)-SM9
[0056] Its synthetic route and method are the same as those of compound (R)-SM9.
[0057] Synthesis of compound (R)-SM10
[0058] In a 200 mL single-necked flask, (R)-SM9 (512 mg, 0.8 mmol), pinacol diborate (485 mg, 1.9 mmol), potassium acetate (750 mg, 7.6 mmol), [1,1'-bis(diphenylphosphine)ferrocene]palladium dichloride (28 mg, 0.04 mmol), and 15 mL of analytical grade toluene solution were added sequentially. The mixture was refluxed at 110 °C for 24 h under nitrogen protection. After the reaction was complete, the mixture was cooled to room temperature, the solvent was evaporated, water was added, and the mixture was extracted with dichloromethane, washed three times with water, dried over anhydrous magnesium sulfate, filtered, and the filtrate was collected. The solvent was evaporated again. The mixture was then slurried between dichloromethane and methanol, and filtered to give 211 mg of a white solid, with a yield of 36.3%. 1H NMR (400MHz, CD2Cl2) δ7.85(d,J=8.2Hz,2H),7.79(d,J=8.8Hz,2H),7.74(d,J=8.0Hz,4H),7.52(d,J=8.0Hz ,4H),7.41(dd,J=17.3,8.1Hz,4H),7.29(t,J=7.5Hz,2H),7.20(s,2H),6.93(d,J=8.8Hz,2H),1.25(s,24H).
[0059] Synthesis of compound (S)-SM10
[0060] Its synthetic route and method are the same as those of compound (R)-SM10.
[0061] Synthesis of compound (R)-F
[0062] In a 25 mL double-necked flask, (R)-SM8 (315 mg, 0.5 mmol), SM6 (300 mg, 0.5 mmol), and tetraphenylphosphine palladium (89 mg, 0.08 mmol) were added sequentially to a mixture of 1,4-dioxane (9.0 mL) and sodium carbonate aqueous solution (3.0 mL, 2 M). The mixture was heated to 95 °C and refluxed for 72 h under an argon atmosphere. Then, phenylboronic acid (65 mg) dissolved in 1 mL of 1,4-dioxane was added to the reaction system using a syringe, and the mixture was refluxed at 95 °C for another 12 h. Next, 1 mL of bromobenzene was added to the mixture, and the mixture was stirred at 95 °C for 12 h. Finally, sodium diethyldithiocarbamate (1.5 g) dissolved in 6 mL of deionized water was added to the reaction system using a syringe, and the mixture was refluxed at 75 °C for 12 h. After the mixture cooled to room temperature, water was added, followed by extraction with chloroform. The combined organic layers were washed sequentially with 1M HCl, 1M NaHCO3, and brine. The mixture was dried over anhydrous magnesium sulfate, filtered, and the solution was concentrated to 5-10 mL by rotary evaporation. The solution was then added dropwise to 250 mL of methanol to precipitate the crude product. The solid was collected by filtration and further purified by Soxhlet extraction (12 h each in acetone and chloroform). The chloroform solution after Soxhlet extraction was concentrated to 5-10 mL, added dropwise to 250 mL of methanol to precipitate, filtered, and dried under vacuum to obtain 227 mg of a gray-green solid, with a yield of 10%. The collected solid could be used for PLED manufacturing without further purification. The 1H NMR spectrum after polymerization showed characteristic peaks for the two methyl groups on acridine at approximately δ 1.77, confirming successful polymerization. (See attached instruction manual for the spectrum.) Figure 14 (a))
[0063] Synthesis of compound (S)-F
[0064] Its synthetic route and method are the same as those of compound (R)-F.
[0065] Synthesis of compound (R)-BP-TATC
[0066] In a 25 mL two-necked flask, (R)-SM8 (335 mg, 0.55 mmol), SM6 (300 mg, 0.55 mmol), tetraphenylphosphine palladium (95 mg, 0.08 mmol), and Aliquant 336 (11 mg, 0.03 mmol) were added sequentially in a mixture of toluene (6.0 mL) and potassium carbonate aqueous solution (3.0 mL, 2 M). The mixture was heated to 85 °C and refluxed for 72 h under an argon atmosphere. Then, phenylboronic acid (65 mg) dissolved in toluene (1 mL) was added to the reaction system using a syringe, and the mixture was refluxed at 85 °C for another 12 h. Next, 1 mL of bromobenzene was added to the mixture, and the mixture was stirred at 85 °C for 12 h. Finally, sodium diethyldithiocarbamate (1.5 g) dissolved in 6 mL of deionized water was added to the reaction system using a syringe, and the mixture was refluxed at 75 °C for 12 h. After the mixture cooled to room temperature, water was added, followed by extraction with chloroform. The combined organic layers were washed sequentially with 1M HCl, 1M NaHCO3, and brine. The mixture was dried over anhydrous magnesium sulfate, filtered, and the solution was concentrated to 5-10 mL by rotary evaporation. The solution was then added dropwise to 250 mL of methanol to precipitate the crude product. The solid was collected by filtration and further purified by Soxhlet extraction (acetone and chloroform, 12 h each). The chloroform solution after Soxhlet extraction was concentrated to 5-10 mL, added dropwise to 250 mL of methanol to precipitate, filtered, and dried under vacuum to obtain 200 mg of a dark yellow solid, with a yield of 9%. The collected solid could be used for PLED manufacturing without further purification. The 1H NMR spectrum after polymerization showed characteristic peaks for the two methyl groups on acridine at approximately δ 1.69 and 0.96, consistent with the peak positions of the two methyl groups on monomer SM6, confirming successful polymerization. (See attached instruction manual for the spectrum.) Figure 14 (b))
[0067] Synthesis of compound (S)-BP-TATC
[0068] Its synthetic route and method are the same as those of compound (R)-BP-TATC.
[0069] Synthesis of compound (R)-BPh-DPS
[0070] In a 25 mL two-necked flask, (R)-SM10 (393 mg, 0.5 mmol), SM4 (300 mg, 0.5 mmol), tetraphenylphosphine palladium (89 mg, 0.08 mmol), and Aliquant 336 (10 mg, 0.03 mmol) were added sequentially in a mixture of toluene (5.0 mL) and potassium carbonate aqueous solution (2.5 mL, 2 M). The mixture was heated to 85 °C and refluxed for 72 h under an argon atmosphere. Then, phenylboronic acid (65 mg) dissolved in toluene (1 mL) was added to the reaction system using a syringe, and the mixture was refluxed at 85 °C for another 12 h. Next, 1 mL of bromobenzene was added to the mixture, and the mixture was stirred at 85 °C for 12 h. Finally, sodium diethyldithiocarbamate (1.5 g) dissolved in 6 mL of deionized water was added to the reaction system using a syringe, and the mixture was refluxed at 75 °C for 12 h. After the mixture cooled to room temperature, water was added, followed by extraction with chloroform. The combined organic layers were washed sequentially with 1M HCl, 1M NaHCO3, and brine. The mixture was dried over anhydrous magnesium sulfate, filtered, and the solution was concentrated to 5-10 mL by rotary evaporation. The solution was then added dropwise to 250 mL of methanol to precipitate the crude product. The solid was collected by filtration and further purified by Soxhlet extraction (12 h each in acetone and chloroform). The chloroform solution after Soxhlet extraction was concentrated to 5-10 mL, added dropwise to 250 mL of methanol to precipitate, filtered, and dried under vacuum to obtain 300 mg of a yellow-green solid, with a yield of 12%. The collected solid could be used for PLED manufacturing without further purification. The 1H NMR spectrum after polymerization showed characteristic peaks for the two methyl groups on acridine at approximately δ 1.80, confirming successful polymerization. (See attached instruction manual for the spectrum.) Figure 14 (c))
[0071] Synthesis of compound (S)-BPh-DPS
[0072] Its synthetic route and method are the same as those of compound (R)-BPh-DPS.
[0073] Example 2
[0074] The compounds (R) / (S)-F, (R) / (S)-BP-TATC, and (R) / (S)-BPh-DPS from Example 1 were heated at a rate of 20°C per minute under N2 in the range of 30–600°C, and their thermogravimetric curves were measured. Figure 1 It can be seen that the decomposition temperatures of compounds (R) / (S)-F at 5% are 393℃ and 417℃, respectively; the decomposition temperatures of compounds (R) / (S)-BP-TATC at 5% are 379℃ and 360℃, respectively; and the decomposition temperatures of compounds (R) / (S)-BPh-DPS at 5% are 249℃ and 379℃, respectively.
[0075] Example 3
[0076] The compound (R) / (S)-F from Example 1 was dissolved in toluene to prepare a solution of 10 -5 Solution M was tested, and its UV-Vis absorption and photoluminescence spectra were measured. Figure 2 (a) It can be seen that the UV-Vis absorption spectrum of compound (R) / (S)-F in solution has approximately two types of absorption peaks: the absorption peak at a short wavelength (260 nm) is mainly attributed to the π-π* transition absorption of the molecule; the absorption peak at a long wavelength (350 nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit within the molecule. For example... Figure 2 As shown in (a), the maximum emission peak of compound (R) / (S)-F is 525 nm, in the green light region. Figure 2 (b) is the photoluminescence spectrum of the compound in a 10% doped PMMA film. The maximum emission peak of the compound (R) / (S)-F is 500 nm in the green region.
[0077] Example 4
[0078] The compound (R) / (S)-BP-TATC from Example 1 was dissolved in toluene to prepare a solution of 10 -5 Solution M was tested, and its UV-Vis absorption and photoluminescence spectra were measured. Figure 3 (a) It can be seen that the UV-Vis absorption spectrum of compound (R) / (S)-BP-TATC in solution has roughly two types of absorption peaks: the absorption peak below short wavelength (300 nm) is mainly attributed to the π-π* transition absorption of the molecule; the absorption peak at long wavelength (350 nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit within the molecule. For example... Figure 3 As shown in (a), the maximum emission peak of compound (R) / (S)-BP-TATC is around 550 nm, in the yellow light region. Figure 3 (b) is the photoluminescence spectrum of the compound in a 10% doped PMMA film. The maximum emission peak of the compound (R) / (S)-F is around 550 nm in the yellow light region.
[0079] Example 5
[0080] The compound (R) / (S)-BPh-DPS from Example 1 was dissolved in toluene to prepare a solution of 10 -5 Solution M was tested, and its UV-Vis absorption and photoluminescence spectra were measured. Figure 4 (a) It can be seen that the UV-Vis absorption spectrum of compound (R) / (S)-BPh-DPS in solution has roughly two types of absorption peaks: the absorption peak below short wavelength (300 nm) is mainly attributed to the π-π* transition absorption of the molecule; the absorption peak at long wavelength (357 nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit within the molecule. For example... Figure 4As shown in (a), the maximum emission peak of compound (R) / (S)-BPh-DPS is around 515 nm, in the green light region. Figure 4 (b) is the photoluminescence spectrum of the compound (R) / (S)-BPh-DPS in a 10% doped PMMA film. The maximum emission peak of the compound (R) / (S)-BPh-DPS is around 505 nm in the green light region.
[0081] Example 6
[0082] The photoluminescence properties of compound (R) / (S)-F from Example 1 were tested in different solutions. Compound (R) / (S)-F was dissolved in toluene, tetrahydrofuran, dichloromethane, trichloromethane, and N,N-dimethylformamide solutions, respectively, and its photoluminescence spectra in different solutions were measured. Figure 5 As shown in the figure, both compounds exhibit significant solvation discoloration with increasing solvent polarity, a typical characteristic of intramolecular CT features in the corresponding excited states. Furthermore, compared to N,N-dimethylformamide solution, the maximum redshift of compound (R)-F in toluene solution is 46 nm, and the maximum redshift of compound (S)-F is 40 nm.
[0083] Example 7
[0084] The photoluminescence properties of compound (R) / (S)-BP-TATC from Example 1 were tested in different solutions. Compound (R) / (S)-BP-TATC was dissolved in toluene, tetrahydrofuran, dichloromethane, trichloromethane, and N,N-dimethylformamide solutions, respectively, and its photoluminescence spectra in different solutions were measured. Figure 6 As shown in the figure, both compounds exhibit significant solvation discoloration with increasing solvent polarity, which is a typical characteristic of the intramolecular CT features in the corresponding excited states. Furthermore, compared to N,N-dimethylformamide solution, the maximum redshift of compound (R)-BP-TATC in toluene solution is 87 nm, and the maximum redshift of compound (S)-BP-TATC is 59 nm.
[0085] Example 8
[0086] The photoluminescence properties of compound (R) / (S)-BPh-DPS from Example 1 were tested in different solutions. Compound (R) / (S)-BPh-DPS was dissolved in toluene, tetrahydrofuran, dichloromethane, trichloromethane, and N,N-dimethylformamide solutions, respectively, and its photoluminescence spectra in different solutions were measured. Figure 7As shown in the figure, both compounds exhibit significant solvation discoloration with increasing solvent polarity, a typical characteristic of intramolecular CT features in the corresponding excited states. Furthermore, compared to N,N-dimethylformamide solution, the maximum redshift of compound (R)-BPh-DPS in toluene solution is 57 nm, and the maximum redshift of compound (S)-BPh-DPS is 55 nm.
[0087] Example 9
[0088] The fluorescence lifetime of compound (R) / (S)-F in Example 1 was tested in a 10% doped PMMA film under a nitrogen atmosphere, as shown in the figure. Figure 8 As shown, the fitting results show that the delayed lifetimes of (R) / (S)-F are 11 and 14 ns, respectively, both of which are short lifetimes.
[0089] Example 10
[0090] The fluorescence lifetime of compound (R) / (S)-BP-TATC in Example 1 was tested in a 10% doped PMMA film under a nitrogen atmosphere, as shown in the figure. Figure 9 As shown in (a), the instantaneous lifetimes of (R) / (S)-BP-TATC, obtained through fitting, are 11 and 9.5 ns, respectively, indicating short lifetimes. Figure 9 As shown in (b), the delayed lifetimes of (R) / (S)-BP-TATC are 4.2 and 4.05 μs, respectively, which are long lifetimes.
[0091] Example 11
[0092] The fluorescence lifetime of compound (R) / (S)-BPh-DPS in Example 1 was tested in a 10% doped PMMA film under a nitrogen atmosphere, as shown in the figure. Figure 10 As shown, the instantaneous lifetimes of (R) / (S)-BPh-DPS, obtained by fitting, are 5.5 and 9 ns, respectively, which are short lifetimes.
[0093] Example 12
[0094] The temperature-dependent lifetime spectra of compound (R) / (S)-BP-TATC in Example 1 were tested in a 10% doped PMMA film under a nitrogen atmosphere, as shown below. Figure 11 As shown, the retardation component increases with increasing temperature, which further proves the TADF characteristics of (R) / (S)-BP-TATC.
[0095] Example 13
[0096] The circularly polarized luminescence properties of the undoped compounds (R) / (S)-F, (R) / (S)-BP-TATC, and (R) / (S)-BPh-DPS from Example 1 were tested. Figure 12 It can be seen that (R) / (S)-F,
[0097] Both (R) / (S)-BP-TATC and (R) / (S)-BPh-DPS have very obvious CPL signals, |g lum | 2.0 × 10 -3 (500nm), 2.9×10 -3 (546nm) and 1.7×10 -3 (518nm).
[0098] Example 14
[0099] The compound (R)-BP-TATC in Example 1 (its |g lum |=2.9×10 -3 Application of (546nm) in organic light-emitting diodes. An organic light-emitting diode with the structure ITO / PEDOT:PSS (40nm) / mCPCN:(10wt%, 20wt%, 30wt% (R)-BP-TATC) / TmPyPB (45nm) / LiF (0.5nm) / Al (120nm) was fabricated using a compound as the dopant for the device's light-emitting layer. In this structure, PEDOT:PSS is the hole injection layer, mCPCN is the host material for the light-emitting layer, TmPyPB is the electron transport layer, and LiF / Al is the cathode. The compound (R)-BP-TATC, with 10wt% doping, achieved a maximum external quantum efficiency of 1.5%. Figure 13 As shown.
[0100] Compound (R)-F in Example 1 (its |g lum |=2.0×10 -3 Application of (500nm) in organic electroluminescent devices. A structure of ITO / PEDOT:PSS was prepared using a compound as the dopant for the device's light-emitting layer.
[0101] Organic light-emitting diodes (OLEDs) using the following doping method: mCPCN: 10wt%, 20wt%, 30wt% RF / TSPO1 (9nm) / TmPyPB (45nm) / LiF (0.5nm) / Al (120nm). In this method, PEDOT:PSS is the hole injection layer, mCPCN is the host material for the light-emitting layer, TSPO1 is the hole blocking layer, TmPyPB is the electron transport layer, and LiF / Al is the cathode. The device with 30wt% doping of compound (R)-F achieves a maximum external quantum efficiency of 0.6%. Figure 13 As shown.
[0102] Although the invention has been described in conjunction with preferred embodiments, the invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the invention. Guided by the inventive concept, those skilled in the art should recognize that any modifications made to the various embodiments of the invention will be covered by the spirit and scope of the claims.
Claims
1. A class of chiral luminescent materials exhibiting space charge transfer effect, characterized in that, The chiral luminescent material is any one of the compounds shown in the following molecular structural formulas: 。 2. A method for preparing a chiral luminescent material with space charge transfer effect according to claim 1, characterized in that, The preparation method is as follows: using a naphthalene derivative as a chiral source, diphenyl sulfone or benzophenone as an electron acceptor, and acridine as an electron donor, a chiral luminescent material with space charge transfer effect was synthesized by the Suzuki-Miyaura reaction.
3. An application of the chiral luminescent material with space charge transfer effect according to claim 1, characterized in that, The chiral luminescent material is used to prepare organic light-emitting diodes.
4. The application of the chiral luminescent material with space charge transfer effect according to claim 3, characterized in that, The light-emitting layer of an organic light-emitting diode (OLED) is prepared by using chiral luminescent materials as dopants in the light-emitting layer through solution processing.
5. The application of the chiral luminescent material with space charge transfer effect according to claim 3, characterized in that, The mass percentage of chiral luminescent material used as a dopant in the luminescent layer is 10-30 wt%.
Citation Information
Patent Citations
Fluorescent material with space charge transfer effect and application thereof
CN112266357A
High-efficiency chiral liquid crystal fluorescent material and application thereof
CN115745885A
